Integrated Risk Assessment for the Blue Economy - Hodgson, Emma E.; Essington, Timothy E.; Samhouri, Jameal F.; Allison, Edward H.; Bennett, Nathan J.; Bostrom, Ann; Cullen, Alison C.; Kasperski, Stephen; Levin, Phillip S.; Poe, Melissa R. (Frontiers in Marine Science, 2019)
With the anticipated boom in the ‘blue economy’ and associated increases in industrialization across the world’s oceans, new and complex risks are introduced to ocean ecosystems. As a result, conservation and resource management increasingly look to factor in potential interactions among the social, ecological and economic components of these systems. Investigation of these interactions requires interdisciplinary frameworks that incorporate methods and insights from across the social and biophysical sciences. Risk assessment methods, which have been developed across numerous disciplines and applied to various real-world settings and problems, provide a unique connection point for cross-disciplinary engagement. However, research on risk is often conducted in distinct spheres by experts whose focus is on narrow sources or outcomes of risk. Movement towards a more integrated treatment of risk to ensure a balanced approach to developing and managing ocean resources requires cross-disciplinary engagement and understanding. Here, we provide a primer on risk assessment intended to encourage the development and implementation of integrated risk assessment processes in the emerging blue economy. First, we summarize the dominant framework for risk in the ecological / biophysical sciences. Then, we discuss six key insights from the long history of risk research in the social sciences that can inform integrated assessments of risk: 1) consider the subjective nature of risk, 2) understand individual social and cultural influences on risk perceptions, 3) include diverse expertise, 4) consider the social scales of analysis, 5) incorporate quantitative and qualitative approaches, and 6) understand interactions and feedbacks within systems. Finally, we show how these insights can be incorporated into risk assessment and management, and apply them to a case study of whale entanglements in fishing gear off the U.S. west coast.